Forward-Looking Information Disclosure: The Role of The Board of Directors - Hapsari, Dian; Setiawan, Doddy; Aryani, Y. Anni (Universitas Muhammadiyah Surakarta, 2024)
This study examines the effect of gender diversity, board size, and frequency of board meetings on forward-looking information disclosure in manufacturing companies in Indonesia. Financial factors such as profitability, leverage, and company age are used as control variables. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period, using purposive sampling method. The results of the panel data regression analysis show that gender diversity and frequency of board meetings have a significant positive effect on the disclosure of forward-looking information, while board size does not show a significant effect. These findings support agency theory which states that higher information disclosure can reduce information asymmetry and agency costs, as well as improve the assessment of future corporate performance.